The effects of technology-integrated classroom instruction on K-12 English language learners' literacy development: a meta-analysis. Issue 5 (4th July 2022) - Lee, Sungyoon; Kuo, Li-Jen; Xu, Zhihong; Hu, Xueyan
Abstract: With the escalating growth of English language learners (ELLs) worldwide, educational technology has been identified as an important learning tool with significant potential to support second language literacy development. This review examined the effectiveness of technology-integrated literacy instruction in the classroom context for ELLs in Grades K-12. Thirty-six articles with 42 independent samples, based on a total of 4, 354 participants, were included in this meta-analysis. Findings confirmed that technology-integrated instruction produced a positive, medium effect size (ES = 0.47) on literacy outcome as compared to traditional methods where no technology was involved. Moderator analyses were conducted with eight study features: grade level, learning context, study duration, intensity per week, total contact time, literacy outcome, pedagogical use, and teaching method. Learning context and literacy outcomes were found to be statistically significant to explain the variance of the effect sizes between the studies. These results advocate for the use of educational technology in literacy instruction for ELLs, regardless of literacy outcomes, pedagogical use, teaching methods, learning contexts, and grade levels. Theoretical and practical implications are discussed.